2022
DOI: 10.1097/01.hjh.0000835956.81410.5e
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Quality of Machine Learning Research and Reporting in Hypertension

Abstract: Objective:Artificial intelligence and machine learning (AI/ML) are increasingly being applied to big clinical data to tackle research questions that cannot be answered with traditional statistical methods. The field is still in its nascent stages and there is a paucity of guidelines for conducting and reporting AI/ML research in hypertension. The objective was to apply the HUMANE checklist to survey the present landscape of AI/ML in hypertension to inform the development of hypertension-specific guidelines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies demonstrated that their algorithms have many-fold higher predictive power when compared with traditional statistical analysis methods. 18–20 However, a study designed to test 5 AI algorithms found that their predictive power was no different to that of traditional regression-based statistical modeling. 21…”
Section: What Is Meant By Precision Hypertension?mentioning
confidence: 99%
“…Recent studies demonstrated that their algorithms have many-fold higher predictive power when compared with traditional statistical analysis methods. 18–20 However, a study designed to test 5 AI algorithms found that their predictive power was no different to that of traditional regression-based statistical modeling. 21…”
Section: What Is Meant By Precision Hypertension?mentioning
confidence: 99%